Familism in Irish capitalism in the 1950s - Kelleher, Patricia (Economic & Social Studies, 1987)
This article is concerned with the Ireland of the 1950s and with one segment of the Irish upper class - the Irish business elite. The importance of studying the 1950s lies in the fact that if there is to be an understanding of the class structure of today the reconstruction of the immediate past is a required precondition. The business elite is defined in terms of those who control Irish corporate capital. Corporate capital is the key form of private property related to economic power. Capital as it relates to the business system is divisible into commercial, industrial and financial interests. Section I of the present article presents the concepts and current debates relating to the issues of capital ownership and control and the role of the family as an important mechanism in the control of, and reproduction, of wealth. Section II discusses methodology and identifies Ireland's top companies in the 1950s. Section III examines patterns of ownership in prominent Irish companies and financial institutions. Finally Section IV identifies Ireland's leading business families of the 1950s and raises questions relating to the nature of dynastic control.
Keywords: Class structure - Ireland; Social mobility - Ireland